Conducta obstétrica ante embarazo de 38.5 semanas con anencefalia. - Jaramillo Pacheco, Petra Carolina (2022)
The following clinical case is based on a 37-year-old female patient, in whom an anencephalic fetus is detected by ultrasound at 18 weeks of gestation at the Hospital del Triunfo and the option of terminating the pregnancy is proposed, however due to ideas Based on personal beliefs, the patient rejected the option and decided to continue with her gestational cycle. In this way, after several weeks of gestation, the patient is referred from the hospital area to the Gynecology emergency area of the "Martin Icaza" Hospital with a diagnosis of pregnancy of +/- 38 weeks of gestation plus neural-type fetal malformation (anencephaly), As part of personal pathological history, he does not refer wrongdoing and as Gyneco-obstetric history it is displayed: gestations 3, childbirth 0, abortion 1, caesarean section 2. When the patient is referred from the first level of care, she does not report any signs or added symptoms, she is prepared for cesarean section after performing fetal monitoring, vital signs control, laboratory tests and communicating to anesthesiology and neonatology. Thus, in the postpartum phase, the patient remains stable, oriented in time, space and afebrile. In this clinical case, the baby from a patient with anencephaly managed to survive around 2 weeks, 4 days, equivalent to a total of 18 days. In Ecuador, according to INEC data, the neonatal mortality rate is 4.6 per 1,000 live births in 2020 and anencephaly is part of the list of causes of neonatal deaths, so this research document focuses on the compilation of data that allow defining causes and risk factors, that help obstetric professionals to take measures that promote optimal health and carry out, as an obstetric professional, the proper referral of patients to treatments in psychological contexts based on providing an environment of emotional support, treatment of disorders related to the loss of a newborn and to accept the diagnosis.